Management process knowledge in the subject area and notion of contextual dependence - Zavuschak, Ira; Zhelizniak, Ira; Rybchak, Zoriana (My University, 2016)
For the best results in any area work should focus on the right combination of people and technology. Context-sensitive methods of control are effective to manage the process of acquiring knowledge. The context act accumulated knowledge or part of the general knowledge base of the organization. Using context provides data and knowledge, which are available at the moment and meaningful for a particular task. The context properties tapering region databases or knowledge bases, emerging area with significant information and therefore the problem that organize solution more quickly and accurately.
Keywords: data; knowledge; context; database; knowledge base